THE BUSINESS MODEL AND ITS ROLE IN THE DEVELOPMENT OF THE INNOVATION POLICY (ANALYSIS OF FOREIGN CONCEPTS) - E. L. Moreva (Финансы: теория и практика)
Nowadays, the development of an effective innovation policy is one of the priority issues of the socioeconomic development of Russia and many other countries. However, despite the efforts made, not all of them succeeded in its solution. In Russia, like in a number of other states, the expert community continue to search  or effective ways to influence microeconomic entities and, above all, businesses that would yield an adequate response. Therefore, any attempt to reveal structures which, when affected, would lead to the increase in the innovative activity of commercial organizations, are not only of theoretical but also of great practical interest. The paper analyzes proposals of foreign authors on the solution of this problem. The foreign approaches under study are focused on the recognition of the business model as a special component of commercial organizations. Its specifics should be taken into account in development and implementation of the state innovation policy in relation to business. As part of a general critical analysis of the approaches, the author summarized and systematized the existing views on the contents of business models, their types and relationships with innovations in organizations. At present, there is no common understanding in the literature that the choice of particular types of business models determining different sources of innovative activity in response to the corresponding state policy requires a prudent attitude and preliminary clarification of a number of additional conditions. The most significant of these include the type of a business model, the stability of its reproduction and position in the industry markets. The conclusions made in the paper require that new important areas of theoretical research into the domestic economy should be developed. They should be directed towards the determination of business model types in different economic sectors, their stability and development of a corresponding state innovation course with respect to them. Along with above, these conclusions lay the foundations for practical efforts to implement innovative strategies developed for enterprizes with different types of business models.